Design process and simulation testing of a shape memory alloy actuated robotic microgripper - Ashraf Fahmy Abdo (Microsystem Technologies, 2019)
Microgrippers are commonly used for micromanipulation of micro-objects with dimensions from 1 to 100 µm and attain features of reliable accuracy, low cost, wide jaw aperture and variable applied force. This paper studies the design process, simulation, and testing of a microgripper which can manipulate and assemble a platinum resistance temperature probe, made from a 25 µm diameter platinum wire, a 20 mm diameter tinned copper wire, and a printed circuit board type connector. Various microgripper structures and actuator types were researched and reviewed to determine the most suitable design for the required micromanipulation task. Operation tests using SolidWorks and ANSYS software were conducted to test a parallelogram structure with flexible single-notch hinges. The best suited material was found to be Aluminium alloy 7075-T6 as it was capable of producing a large jaw tip displacement of 0.7 mm without exceeding its tensile yield strength limit. A shape memory alloy was chosen as a choice of actuator to close the microgripper jaws. To ensure a repeatably accurate datum point, the final microgripper consisted of a fixed arm and a flexible arm. An optimisation process using ANSYS studied the hinge thickness and radius dimensions of the microgripper which improved its deflection whilst reducing the experienced stress.